Survey on the awareness of COVID-19 virus infection among the health personnel of Sirajganj area, Bangladesh - Ali, Shaikh M. Eunus; Akter, Dilara; Bhuiyan, Mohammad Kamal Uddin; Rahman, Inamur; Sarker, Nabid Shahriar; Rubab, Khadiza (International Journal of Research in Medical Sciences, 2024)
Background: The COVID-19 pandemic has posed significant challenges to healthcare systems worldwide, particularly in resource-limited settings. Understanding the awareness and practices of health personnel regarding COVID-19 is crucial for effective infection control and patient care. This study aims to assess the awareness of COVID-19 symptoms, complications, transmission methods, and preventive practices among health personnel in Sirajganj, Bangladesh. Methods: This descriptive cross-sectional study involved 260 health personnel from Shaheed M. Monsur Ali Medical College and the 250 Beded Sheikh Fazilatunnesa Mujib General Hospital, Sirajganj. Data were collected through a semi-structured questionnaire, focusing on COVID-19 awareness and practices. The study employed purposive sampling and face-to-face interviews for data collection. Results: The study found high awareness of COVID-19 symptoms, with 96.15% recognizing fever and 97.69% identifying loss of smell. Awareness of complications like respiratory failure (80.00%) and pneumonia (60.77%) was also notable. Preventive practices such as handwashing (98.08%) and mask-wearing (98.08%) were widely adhered to. However, 36.15% of participants reported being affected by COVID-19, indicating potential exposure risks. Conclusions: The study reveals a high level of awareness and adherence to COVID-19 preventive measures among health personnel in Sirajganj. Despite this, the infection rate among participants highlights the need for enhanced protective measures and continuous education. These findings can inform strategies to strengthen healthcare responses to ongoing and future pandemics.